1996
DOI: 10.1037/0021-843x.105.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Display visual angle and attentional scanpaths on the span of apprehension task in schizophrenia.

Abstract: The effect of display visual angle on span of apprehension (SOA) task performance was investigated in patients with schizophrenia and nonpsychiatric individuals. Narrow and wide visual-angle presentations of 3- and 10-letter arrays were compared. Detection rates were significantly higher with narrow than wide visual angle for nonpsychiatric individuals; the performance of those with schizophrenia was stable across visual-angle conditions. Patients with schizophrenia were best discriminated from nonpsychiatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…This is consistent with reports of peripheral vision deficits in schizophrenia patients [9]–[11], [15]. Therefore, we hypothesized that sensory processing of information from the visual periphery would be impaired in schizophrenia patients and, as a result, crowding would be stronger than in healthy individuals.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is consistent with reports of peripheral vision deficits in schizophrenia patients [9]–[11], [15]. Therefore, we hypothesized that sensory processing of information from the visual periphery would be impaired in schizophrenia patients and, as a result, crowding would be stronger than in healthy individuals.…”
Section: Introductionsupporting
confidence: 88%
“…Previous studies on visual information processing in schizophrenia have largely neglected peripheral vision, and information regarding the presence, extent and nature of peripheral visual dysfunction in schizophrenia is incomplete and inconsistent [9]–[15]. For example, although Miller et al [14] found no difference between central and peripheral visual processing in schizophrenia patients, Elahipanah et al [10] found disproportionately large deficits when target stimuli were located peripherally, and Granholm et al [11] identified peripheral deficits in schizophrenia patients that were most prominent when object density in the visual field was high. It therefore appears as though peripheral vision may be impaired in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major determinants of deficient performance on the partial report version of the SPAN task is proposed to be in some aspect of serial scanning processes (Asarnow et al , 1991). Support for serial scanning being central in the SPAN task is found in studies of scanpaths that show that people in general tend to make more mistakes in the bottom than in the top quadrants (Estes & Taylor, 1964; Granholm, Asarnow & Marder, 1996; Asarnow & Sherman, 1984). It has also been shown that it is in the larger array conditions (10‐ and 12‐letters), requiring a high processing load, that schizophrenic patients are best discriminated from non‐psychiatric individuals (Asarnow et al ., 1981; Granholm et al , 1996).…”
mentioning
confidence: 99%
“…Two of the studies (Elahipanah et al 2010; Granholm et al 1996) showed that patients had degraded performance for detecting peripheral visual targets, but another study (Miller et al 1990) showed relatively intact visual detection in periphery. Interestingly, under backward masking conditions, both patients (Butler et al 1996; Green et al 1994a) and their siblings (Green et al 1997; Green et al 2006; Sponheim et al 2013) showed impairments in perception of the target location and target identification, with the targets presented at multiple possible peripheral locations.…”
Section: Introductionmentioning
confidence: 99%